2015
DOI: 10.1021/acs.jpclett.5b00750
|View full text |Cite
|
Sign up to set email alerts
|

Same-View Nano-XAFS/STEM-EDS Imagings of Pt Chemical Species in Pt/C Cathode Catalyst Layers of a Polymer Electrolyte Fuel Cell

Abstract: We have made the first success in the same-view imagings of 2D nano-XAFS and TEM/STEM-EDS under a humid N2 atmosphere for Pt/C cathode catalyst layers in membrane electrode assemblies (MEAs) of polymer electrolyte fuel cells (PEFCs) with Nafion membrane to examine the degradation of Pt/C cathodes by anode gas exchange cycles (start-up/shut-down simulations of PEFC vehicles). The same-view imaging under the humid N2 atmosphere provided unprecedented spatial information on the distribution of Pt nanoparticles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 30 publications
4
53
0
Order By: Relevance
“…(B) 2D‐mappings of Pt concentration and valence state in an MEA cathode catalyst layer derived by the Pt L III ‐edge scanning nano‐XAFS technique . (C) 3D‐light‐element distribution in the MEA cathode catalyst layer derived by X‐ray ptycho‐tomography technique …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) 2D‐mappings of Pt concentration and valence state in an MEA cathode catalyst layer derived by the Pt L III ‐edge scanning nano‐XAFS technique . (C) 3D‐light‐element distribution in the MEA cathode catalyst layer derived by X‐ray ptycho‐tomography technique …”
Section: Introductionmentioning
confidence: 99%
“…The XAFS imaging and EXAFS analysis at selected parts successfully identified where catalyst degradation and dissolution proceeded during accelerated degradation test (ADT), which is a typical protocol to accelerate cathode catalyst degradation in a practical PEFC cell . The complementary scanning nano‐XAFS and scanning transmission electron microscopy‐energy dispersive X‐ray spectroscopy (STEM‐EDS) imaging clearly showed that the dissolved oxidized species and detached metallic nanoparticles were observed in the Nafion ionomer of the degraded cathode catalyst layer …”
Section: Introductionmentioning
confidence: 99%
“…The extent to which catalyst activity and durability measurements under idealized conditions transfer directly to the hot, gas-phase polymer electrolyte MEA environment remains an open question, and the answer will guide the development of active materials and operating protocols toward more robust performance. While much is known about degradation occurring specifically inside MEAs, ,,,,, a direct cell performance prediction based on rotating disc electrode studies remains challenging, especially for nanostructured catalysts, due to the phenomena discussed above.…”
mentioning
confidence: 99%
“…Techniques that can simultaneously probe all the components of functional devices at the nanoscale are urgently required to optimize the MEA architecture and operating conditions. Spectromicroscopy approaches using electron, neutron, and photon beams ,, are powerful but generally laborious and/or limited to ex situ experiments. Significant advances in spatial and time resolution with in situ X-ray absorption tomography have been recently achieved. , However, spatial resolution is often limited to scales greater than 100 nm and lacks the critical nanoscale and chemical information about the catalyst and supporting materials.…”
mentioning
confidence: 99%
“…These findings were recently integrated with a same-view nano-XAFS and STEM-EDS investigation. [67] Here, the chemical information obtained with the quick-XAFS measurements was complemented with the atomic-scale details achieved via a STEM analysis, both carried out in the same location. …”
Section: Imaging the Catalyst Degradationmentioning
confidence: 99%